Buku panduan penggunaan dan pengisian buku rekod kesihatan ibu hamil - Ismail, Hamizah; Yusof@Abdullah Saari, Azianey; Mohamed, Majdah; Nawawi, Mariam; Hashim, Nor Asiah; Kamaruzaman, Nor Azam; Karimon, Noor Aini; Awang Dahlan, Sarah; Mohsinon, Tuty Aridzan Irdawati; Muhamad, Amalina; Ali, Aleijjah; Barukang, Kamisah; et al. (Bahagian Pembangunan Kesihatan Keluarga, Kementerian Kesihatan Malaysia, 2019)
The usage of clinic based Antenatal Record Book in Malaysia was started in 1st June 1993. It supposedly contains the complete information on antenatal care received by a pregnant woman. This was later changed to home based record in 1997. Comprehensive review of this Antenatal Record Book were made in 2012 and again in 2019 in conjunction with the ever dynamic health technologies.